Juridical analysis of land rights according to UPPA in Indonesia - Nurwati Nurwati; Wafda Vivid Izziyana; alma juliana; angga subianto; lailatul fitri (Universitas Muhammadiyah Gresik, 2022)
The right of ownership is already known in customary law, which is as a result of the development of control and exploitation or use as communal land intensively and continuously by individual citizens of customary law communities holders of communal rights. This study uses normative juridical methods, while the results of this study manganalisis that property rights are basically reserved exclusively for Indonesian citizens who are single citizens, which is used as cultivated land or to build something on it. In accordance with the nature of the Bal (basic agrarian law or UUPA), property rights are determined not limited to the validity period, can be transferred and transferred and can also be burdened with mortgage rights. Use rights with the designation HGU & HGB do not contain emotional psychological, such as property rights. The relationship of the right holder with the land being valued is merely a straightforward relationship, that is, simply to enable the right holder to use it to meet certain needs. The right to use non-property rights is also known in customary law. various needs for land, then to make it easier to recognize the designation, the right to use it in accordance with the typical designation of each land is named a different designation, namely the right to use the land to cultivate, the right to build to build something on it. In the Bal both rights are limited in validity and can be granted other than Indonesian citizens and Indonesian legal entities. Hak Pakai is given the specificity of the nature or designation of the use of its land, or on consideration of the point of use of its land that cannot be granted with HM, HGU and HGB, hence the name Hak Pakai. There are also temporary land rights. It is said that it is temporary, which means that at some time these rights as legal institutions will no longer exist, since they are considered incompatible with the principles of HTN.